A responsive living material prepared by diffusion reveals extracellular enzyme activity of cyanobacteria - Lisa Tang; Nathan T. Soulier; Rebecca Wheeler; Jonathan K. Pokorski; James W. Golden; Susan S. Golden; Jinhye Bae (Proceedings of the National Academy of Sciences, 2025)
Stimuli-responsive engineered living materials (ELMs) can respond to environmental or biochemical cues and have broad utility in biological sensors and machines, but have traditionally been limited to biocompatible scaffolds. This is because they are typically made by mixing cells into a precursor solution before crosslinking. Here, we demonstrate a diffusion mechanism for incorporating cells of the cyanobacterium Synechococcus elongatus sp. PCC 7942 ( S. elongatus ) into nanoclay-poly-N-isopropylacrylamide (NC-PNIPAm), a hydrogel with a cytotoxic precursor, by exploiting its temperature-dependent shape-morphing behavior. Subsequent growth of S. elongatus caused a decrease in the bending curvature and stiffness (local Young’s modulus) of NC-PNIPAm due to partial degradation by an unannotated enzyme. Creation and observation of this cyanobacteria-hydrogel ELM showcases a method for diffusing cells into a hydrogel as well as characterizing an extracellular enzyme.